(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article presents a clinical observation and the result of surgical treatment of a rare type of helminthiasis in our country. It is dirofilariasis which was observed in a young woman. The woman suffered from this pathology for a year. As a result of surgical treatment, she was able to get rid of excruciating pain and itching.